2021
DOI: 10.1177/1352458521991433
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus lesions in 16 MS patients treated with fingolimod: Outcomes and vaccination

Abstract: Few cases of human papillomavirus (HPV) diseases have been reported in multiple sclerosis (MS) patients treated with fingolimod. We describe a case series of 16 MS patients (11 women, 5 men) developing HPV lesions after the onset of fingolimod, without previous HPV history. Fingolimod had to be discontinued in six patients. Six patients received vaccination for HPV, with good tolerance. Our report highlights that systematic HPV screening and discussion about HPV vaccination before fingolimod onset are crucial.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
(2 reference statements)
0
9
0
Order By: Relevance
“…Physician advice has been shown to be the most important predictor of vaccine acceptance (Health, 2019). We suggest context-specific vaccination counselling for pwMS, namely (i) avoiding infection-associated additional disability accrual during MS relapses (Reyes et al, 2020); (ii) reducing the potentially higher risk of life-threatening/treatment-refractory complications (e.g., measles encephalitis, mumps meningitis/orchitis/oophoritis, HPV-associated chronic warts and malignancies) (Yang et al, 2020;Mhanna et al, 2021) that may be observed in those who develop vaccine-preventable infections while receiving certain DMTs; and (iii) avoiding attenuated vaccine responses or delayed/interrupted DMT with early pre-treatment vaccine delivery where possible (Riva et al, 2021). Moreover, effective vaccine promotion messaging should be delivered simply without medical jargon, with misconceptions corrected in a timely manner and supported by scientific evidence (Volpp et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physician advice has been shown to be the most important predictor of vaccine acceptance (Health, 2019). We suggest context-specific vaccination counselling for pwMS, namely (i) avoiding infection-associated additional disability accrual during MS relapses (Reyes et al, 2020); (ii) reducing the potentially higher risk of life-threatening/treatment-refractory complications (e.g., measles encephalitis, mumps meningitis/orchitis/oophoritis, HPV-associated chronic warts and malignancies) (Yang et al, 2020;Mhanna et al, 2021) that may be observed in those who develop vaccine-preventable infections while receiving certain DMTs; and (iii) avoiding attenuated vaccine responses or delayed/interrupted DMT with early pre-treatment vaccine delivery where possible (Riva et al, 2021). Moreover, effective vaccine promotion messaging should be delivered simply without medical jargon, with misconceptions corrected in a timely manner and supported by scientific evidence (Volpp et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, while it is routine to screen for varicella zoster immunity and cervical cytology/human papillomavirus (HPV) status before starting immunosuppressive therapies in pwMS (Riva et al, 2021), screening for immunity against measles, mumps and rubella (MMR) is not standard practice; this is concerning given the resurgence of measles and mumps outbreaks in Europe and worldwide, partly attributable to historical missed MMR vaccine doses and waning vaccinal immunity (Reyes et al, 2020;Yang et al, 2020). Secondly, pre-treatment HPV vaccination is not routine despite emerging reports of HPV-associated cutaneous/anogenital/oromucosal warts and malignancies, and cervical dysplasia, in pwMS on fingolimod (Mhanna et al, 2021). Finally, the propensity for respiratory tract infections in pwMS receiving B-cell-depleting therapies suggests that obligatory pre-treatment pneumococcal vaccination may well be warranted (Reyes et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Both cases highlight treatment refractory warts in patients on fingolimod for MS, as previously reported. [4][5][6] We retrospectively identified warts in 7/336 patients (2.1%) receiving fingolimod at our centre between 2011-2019. Treatment was modified in four patients; Two patients discontinued fingolimod with either improvement or resolution, although one subsequently relapsed.…”
mentioning
confidence: 99%
“…[7,8] Causality between fingolimod and warts remains unproven, but is supported by the temporal relationship between treatment modification and improvement in warts. [4][5][6] Fingolimod may impair the immune response to HPV through lymphocyte sequestration, mediated by sphingosine-1-phosphate (S1P) receptor antagonism, and cause warts through chronic infection and clonal proliferation of keratinocytes. Fingolimod may also increase the risk of HPV-driven malignancy [1,6] through impaired T-cell mediated cancer surveillance.…”
mentioning
confidence: 99%
See 1 more Smart Citation